Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1183/09031936.98.12020502
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic lung disease associated with Candida albicans allergy

Abstract: There are few references in the literature about the role of Candida albicans (CA) in eosinophilic lung disease. Asthma related to immunoglobulin (Ig)E-mediated allergy to CA [1] as well as allergic bronchopulmonary candidiasis has been described [2], but the implication of CA in chronic eosinophilic pneumonia has not been previously reported. In this paper we report on a patient in whom chronic eosinophilic pneumonia developed and levels of specific anti-CA IgE in the serum paralleled the clinical course of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Eosinophilic pneumonia with extensive lung shadowing associated with a marked BAL and blood eosinophilia, which is highly glucocorticoid sensitive, is a well-recognised complication of AFAD and has also been described in the context of IgE sensitisation to C. albicans . 115 , 116 A large dose of inhaled A. fumigatus spores, for example in the context of gardening or indoor contamination, can sometimes be identified as a trigger. Similarly, lobar collapse due to large-airway obstruction with inspissated mucus is a classical if unusual presentation.…”
Section: Clinical Features Of Afadmentioning
confidence: 99%
“…Eosinophilic pneumonia with extensive lung shadowing associated with a marked BAL and blood eosinophilia, which is highly glucocorticoid sensitive, is a well-recognised complication of AFAD and has also been described in the context of IgE sensitisation to C. albicans . 115 , 116 A large dose of inhaled A. fumigatus spores, for example in the context of gardening or indoor contamination, can sometimes be identified as a trigger. Similarly, lobar collapse due to large-airway obstruction with inspissated mucus is a classical if unusual presentation.…”
Section: Clinical Features Of Afadmentioning
confidence: 99%
“…No common causative factor or linkage has been described as yet in the literature. Selective sensitization to C. albicans , however, has been demonstrated in chronic eosinophilia pneumonia 8 . Levels of specific immunoglobulins against C. albicans were shown to diminish with corticosteroid treatment and increase with a recurrence of symptoms upon lowering of the corticosteroid dosage 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Selective sensitization to C. albicans , however, has been demonstrated in chronic eosinophilia pneumonia 8 . Levels of specific immunoglobulins against C. albicans were shown to diminish with corticosteroid treatment and increase with a recurrence of symptoms upon lowering of the corticosteroid dosage 8 . More recently, cytokine profiles have shown that the C. albicans allergen may be involved in airway eosinophilic inflammation through the induction of the interleukin (IL)‐5 cytokine production by T helper cells 9 .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Since then, many factors such as drugs, cigarette smoke, and fungi have been implicated as causes of AEP. 3,4 There are few references in the literature regarding the role of Candida albicans in eosinophilic lung disease, 5 although it is well known that C. albicans is one of the aeroantigens that causes bronchial asthma and allergic bronchopulmonary candidiasis. 6 We present here the first case of acute onset eosinophilic pneumonia induced by C. albicans.…”
Section: Introductionmentioning
confidence: 99%